School relationships, communication with parents and prosociality as predictors of positive emotions in adolescents - Ruvalcaba-Romero, Norma Alicia (2018)
The aim of this study was to identify the predictive value of the relationships between classmates, the affective communication with parents and the generation of prosocial behavior have on the experimentation of positive emotions in adolescents. The sample included 490 middle school students from the Metropolitan Area of Guadalajara. We used the measurement instruments: subscale Relations from the Social Climate Scale, the Affective communication subscale from the Affect Scale, in its version for children; the Positive Behavior Scale and, the Positive Emotion Survey. We used correlation tests and multiple linear regression by the method of successive steps for statistical analysis. Results showed a positive and statistically significant correlation between the variables of affiliation and help, prosocial behavior and affective communication with both parents, and, the experimentation of positive emotions: joy and good humor (p< .01). The communication based in criticism with both parents reported statistically significant negative correlations (p< .01). In the multiple linear regression analysis, we found that prosocial behavior and affective communication with the mother are variables that predict positive emotions (R2 = .246). In conclusion, this study found that both, prosocial behavior and positive bonds with the mother, predict the experience of positive emotions.